PERANCANGAN ULANG TATA LETAK FASILITAS PRODUKSI MENGGUNAKAN METODE ALGORITMA CRAFT PADA PT. SERMANI STEEL MAKASSAR - Ahmad Padhil; Andi Pawennari; Takdir Alisyahbana; Firman Firman (Universitas Putera Batam, 2021)
Factory layout is one of the most important problems in a company, because the arrangement of facilities affects the efficiency and cost of manufacturing products. PT. Sermani Steel of Makassar City is one of the companies engaged in the manufacture or production of zinc-coated steel sheets (Zn) with a production capacity of 3000 tons/year, the problem that occurs is that the layout of related departments is far apart, causing large moving costs. The CRAFT Algorithm method is an improvement program that seeks optimum planning by making improvements in stages with the help of the WinQsb software. The CRAFT algorithm method can describe each department and calculate the Material Handling Cost (OMH) experienced by the product during the production process. Based on the results of research conducted, the cost of moving materials in the initial layout is Rp. 1,636,270,800/year after repairing the layout of the facility, the transfer fee is Rp. 1,467,309,300/year with a difference of Rp. 168,961,500 per year, material transfer costs have decreased by 10% from the initial layout.